Using organoids to investigate human endometrial receptivity - Guo, Junhan; Zhou, Wei; Sacco, Michaela; Downing, Poppy; Dimitriadis, Evdokia; Zhao, Feifei (Frontiers in Endocrinology, 2023)
The human endometrium is only receptive to an implanting blastocyst in the mid-secretory phase of each menstrual cycle. Such time-dependent alterations in function require intricate interplay of various factors, largely coordinated by estrogen and progesterone. Abnormal endometrial receptivity is thought to contribute to two-thirds of the implantation failure in humans and therefore significantly hindering IVF success. Despite the incontrovertible importance of endometrial receptivity in implantation, the precise mechanisms involved in the regulation of endometrial receptivity remain poorly defined. This is mainly due to a lack of proper in vitro models that recapitulate the in vivo environment of the receptive human endometrium. Organoids were recently established from human endometrium with promising features to better mimic the receptive phase. Endometrial organoids show long-term expandability and the capability to preserve the structural and functional characteristics of the endometrial tissue of origin. This three-dimensional model maintains a good responsiveness to steroid hormones in vitro and replicates key morphological features of the receptive endometrium in vivo, including pinopodes and pseudostratified epithelium. Here, we review the current findings of endometrial organoid studies that have been focused on investigating endometrial receptivity and place an emphasis on methods to further refine and improve this model.